Exploring Entrepreneurial Interest in Vocational School Students: The Impact of Education, Family Role Models, and Self-Efficacy - Abdul Wahab Shobiri; Agus Hermawan; Nurika Restuningdiah (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study focused on grade 11 and 12 students from vocational schools in Banyuwangi area who face mental health issues that affect their interest in business. This study aims to fill a gap in the existing literature by examining the impact of business education and family structure on students' entrepreneurial interest, with self-efficacy as the conversational variable. Furthermore, this study found that the successful family model increased interest in entrepreneurship and highlights the importance of family values. Furthermore, entrepreneurship education and family structure have a positive impact on students' self-efficacy and enhance their entrepreneurship. This shows that promoting good entrepreneurship education and improving family structure can improve the self-efficacy and entrepreneurial interest of students working in Banyuwangi region. This study not only contributes to academic discourse by addressing specific challenges faced by working students, but also provides insight for policymakers and educators to determine interventions that promote entrepreneurship, self-efficacy, and work independent in specific populations.